CHANGES IN MOTHER CARE PRACTICES FOR CHILDREN UNDER 5 YEARS OLD WITH MIDDLE EAR INFECTIONS AFTER HEALTH EDUCATION CONSULTATION AT FAMILY MULTISPECIALTY HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current situation and evaluate the change in care practices among mothers with children under 5 years old suffering from otitis media after health education counseling at Da Nang Family General Hospital.Subjects and methods: A pre-post evaluation, single-group educational intervention study was conducted on 76 mothers of children under 5 years old with otitis media who were hospitalized at the Family General Hospital, Da Nang from March to April 2025.Results: After the intervention, mothers' practices regarding the care of children under 5 years old with otitis media changed significantly compared to before the intervention (p
Keywords: practice, care, otitis media, health education advice.